Bibliometric Analysis: Risk Factors for Cerebrovascular Accidents in Adolescents - Hafizhah, Nadia Fairus; Irfantiara, Audiannisa; Widyanafi, Afina Rahmah; Napitupulu, Kristin Citra; Sulastri, Augustina; Kusrohmaniah, Sri (Jurnal Keperawatan Respati Yogyakarta, 2025)
This study examines the risk factors associated with cerebrovascular disease (CVA), more commonly referred to as stroke, in adolescents. CVA constitutes the leading cause of neurological disorder in nearly all countries worldwide, representing a significant contributing factor to disability and mortality. Although the incidence of stroke is higher in the older population, there has been an increase in the number of cases affecting younger individuals, particularly adolescents. This study aimed to identify the risk factors contributing to stroke in this age group between 2014 and 2024, using a bibliometric analysis. This study employed VOSviewer and Publish or Perish for bibliometric analysis of publications retrieved from the Scopus database. The results indicated that hypertension, diabetes mellitus, dyslipidemia, smoking and alcohol consumption were the factors most extensively studied to their role as risk factors. Furthermore, there was a significant correlation between these factors and stroke in adolescents. The US was identified as the leading country in this area of research, followed by Canada and the UK. This aims to enhance comprehension of this emerging public health issue and implement strategies for its mitigation. By identifying the causes of CVAs in adolescents, this study provides a foundation for future research aimed at reducing the incidence of stroke in younger populations.